THE DESCRIPTION OF STUDENTS’ METACOGNITION IN MATHEMATICS PROBLEM SOLVING BASED ON PARENTS’ PARENTING PATTERNS - Basri, Erni (Universitas Negeri Makassar, 2018)
The research aims to describe students’ metacognition in mathematics problem solving based on parents’ parenting patterns. The subjects who were described in the research consisted of 4 students with each had parenting pattern of authoritative type, authoritarian type, permissive type, and rejecting/neglecting type. The data were collected by giving one problem solving test and interview. To review the credibility of the data, it was conducted source and time triangulation. The conclusion based on the results of the test and interview are: (1) Metacognition skills of the subject with parents’ parenting pattern of authoritative type are planning, predicting, monitoring, and evaluating skills; (2) Metacognition skills of the subjects with parents’ parenting pattern of authoritarian type and permissive type are planning, predicting, and monitoring skills; (3) Metacognition skills of the subject with parents’ parenting pattern of permissive type are planning and predicting skills